Narcotics trafficking and the American mafia: the myth of internal prohibition - Jenkins, Philip (Crime, law and social change, 1992)
Numerous books assert that the Mafia long had a prohibition against engaging in narcotics trafficking, either for reasons of morality, or else because of the public stigma attached to drugs. In reality, there are many problems with the belief in voluntary abstention. The mythical nature of "internal prohibition", and the far different reality, will be illustrated from the case of Philadelphia, supposedly the base for one of the most powerful and traditional-minded of all the American Mafia groups, the "family" headed from 1959 to 1980 by don Angelo Bruno. We will attempt to explain the roots of the prohibition myth, both for writers and for the wider public that appears so endlessly enthusiastic about sagas of organized crime. Finally, the paper examines the implications of this myth for policy makers in successive "wars on crime".